ChemInform Abstract: Detection of the Elusive Highly Charged Zintl Ions Si44‐ and Sn44‐ in Liquid Ammonia by NMR Spectroscopy. Issue 28 (21st June 2013) - Neumeier, Maria; Fendt, Franziska; Gaertner, Stefanie; Koch, Carina; Gaertner, Tobias; Korber, Nikolaus; Gschwind, Ruth M.
Abstract Dissolution of Rb4Sn4 in liquid ammonia and dissolution of K6Rb6Si17 in liquid ammonia in the presence of [2.2.2]‐cryptand leads to the formation of charged Zintl ions Sn44‐ and Si44‐, respectively.